Establishment of PT. Ulil Albab Management in Community Empowerment Efforts - Samsul Hady; Ahmad Amir Aziz; Muhammad Azkar (STKIP Taman Siswa Bima, 2025)
Community empowerment is an important strategy in an effort to reduce social inequality and improve the quality of life of the community. This article discusses the establishment of PT. Ulil Albab Management as an empowerment model based on Islamic values ​​and the principle of sustainability. PT. Ulil Albab Management was established with the aim of empowering the community through the development of local economic capacity, especially in the micro, small, and medium enterprises (MSMEs) sector. The method used in this study is a qualitative approach with a field study type, so that data collection related to PT. Ulil Albab Management's efforts in community empowerment is carried out through observation, interviews, and documentation. The results of this study indicate that the existence of PT. Ulil Albab Management is not only oriented towards increasing income, but also emphasizes the instillation of Islamic values ​​such as prioritizing business halalness, sharia transactions, profit sharing, and financial management as the main foundation in every economic activity carried out. In terms of community empowerment, the existence of PT. Ulil Albab Management plays an important role in the process of improving skills, developing businesses, and strengthening local economic networks. Therefore, this study is expected to be able to provide knowledge about the importance of integration between community empowerment strategies and professional business management.